2016
DOI: 10.1073/pnas.1604748113
|View full text |Cite
|
Sign up to set email alerts
|

Chemical shift imprint of intersubunit communication in a symmetric homodimer

Abstract: Allosteric communication is critical for protein function and cellular homeostasis, and it can be exploited as a strategy for drug design. However, unlike many protein-ligand interactions, the structural basis for the long-range communication that underlies allostery is not well understood. This lack of understanding is most evident in the case of classical allostery, in which a binding event in one protomer is sensed by a second symmetric protomer. A primary reason why study of interdomain signaling is challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(47 citation statements)
references
References 34 publications
1
46
0
Order By: Relevance
“…However, several lines of evidence show that the effects of substrate or cofactor binding are indeed communicated to the second subunit based on the following: 1) Changes in in enthalpy (and entropy) are not equivalent for the two binding events. 2) We observe quartets of resonances for a subset of amides at intermediate points in diligand NMR titrations (22, 62). Two of the resonances correspond to the free and doubly bound enzymes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several lines of evidence show that the effects of substrate or cofactor binding are indeed communicated to the second subunit based on the following: 1) Changes in in enthalpy (and entropy) are not equivalent for the two binding events. 2) We observe quartets of resonances for a subset of amides at intermediate points in diligand NMR titrations (22, 62). Two of the resonances correspond to the free and doubly bound enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…The other two are attributable to the free and bound subunits of the singly bound state, indicating that binding of the first diligand binding event is communicated to the second subunit. 3) Studies in which we used mixed dimers to isolate the singly bound dUMP state and measure the chemical shifts of all microstates also show crosstalk between binding and non-binding subunits (62). Thus the structure and/or dynamics of the second subunit are affected by binding the first dUMP, cofactor, or diligand molecules.…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence from NMR spectroscopy that structural changes resulting from substrate binding propagate to and across the dimer interface in wild type EcTS as well 5, 26 . During titration of EcTS with the mechanism-based di-ligand inhibitor 5-fluoro-dUMP•mTHF, resonances not present in symmetric apo or doubly bound EcTS for several residues at or near the dimer interface could be assigned to a singly bound state 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Similar but more exaggerated structural differences near the active site cysteine were observed in the asymmetric ternary complex of Pneumocystis carinii TS, which had CB3717 bound in only one active site, and the differences were proposed to be responsible for the half-the-sites reactivity of the enzyme 27 . NMR spectroscopy of EcTS heterodimers with inactivating mutations at one active site revealed that upon binding a single dUMP molecule, subtle structural changes occurred in these same interface residues 26 . This result suggests the residues may constitute a common pathway for communicating between active sites in EcTS, its C-terminal mutants, and other TS species.…”
Section: Resultsmentioning
confidence: 99%
“…In principle, NMR titrations could also track dUMP binding, but we found that dUMP binds with kinetics that lead to chemical exchange mostly in the fast-intermediate timescale. As a result, peaks often became faint or disappeared in the midpoints of the dUMP titration, and quantitative interpretation was difficult or impossible (Falk et al, 2016 ). ITC yielded high-sensitivity data that could be fitted to multiple binding models (Figure 3 ).…”
Section: Quantifying Substrate Binding Cooperativity In Ectsmentioning
confidence: 99%